2017
DOI: 10.1111/ijpo.12214
|View full text |Cite
|
Sign up to set email alerts
|

IRX3 is a genetic modifier for birth weight, adolescent obesity and transaminase metabolism

Abstract: IRX3 genetic variants associate with birth weight, BMI and AST/ALT-related transaminase metabolism, supporting the role of IRX3 as an obesity-associated susceptibility gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
1
4
0
1
Order By: Relevance
“…A 10% increase in overweight or obesity frequency was found when rs3751723 genotype changed from GG to TT. This result coincides with recent studies from multiple populations in which the IRX3 genomic region has been related to anthropometric traits and obesity 14,28,36 . Considering that this gene has been identified as a plausible effector for the influence of FTO on bodyweight [10][11][12][13] , the current genetic associations might be evidence supporting the biological role of IRX3 on weight control as it has been suggested in animal models 12,13 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…A 10% increase in overweight or obesity frequency was found when rs3751723 genotype changed from GG to TT. This result coincides with recent studies from multiple populations in which the IRX3 genomic region has been related to anthropometric traits and obesity 14,28,36 . Considering that this gene has been identified as a plausible effector for the influence of FTO on bodyweight [10][11][12][13] , the current genetic associations might be evidence supporting the biological role of IRX3 on weight control as it has been suggested in animal models 12,13 .…”
Section: Discussionsupporting
confidence: 92%
“…Se encontró un aumento del 10% en la frecuencia de sobrepeso u obesidad cuando el genotipo rs3751723 cambió de GG a TT. Este resultado coincide con estudios recientes de múltiples poblaciones en los que la región genómica IRX3 se ha relacionado con rasgos antropométricos y obesidad 14 , 28 , 36 ). Teniendo en cuenta que este gen ha sido identificado como un efector plausible para la influencia de FTO en el peso corporal ( 10 - 13 ), las asociaciones genéticas actuales podrían ser evidencia que apoya el papel biológico de IRX3 en el control de peso, como se ha sugerido en modelos animales 12 , 13 .…”
Section: Discussionunclassified
“…It was observed that there was a relationship between IRX3, new-born birth weight and body max index (BMI). Genotypes rs8053360 CC and rs1126960 GG were related to body weight and BMI, particularly among females [29]. In another study by Srivastava et al , participants were divided into two groups (overweight and normal weight subjects) in order to investigate the relationship between IRX3 and obesity.…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that there was a relationship between IRX3 , newborn birth weight and BMI. Genotypes rs8053360 CC and rs1126960 GG were related to body weight and BMI, particularly among female individuals ( 46 ), and the polymorphism rs3751723 in IRX3 has been associated with obesity ( 47 ). In the present study, immunohistochemical staining and RNA-seq results from liver tissue showed that the expression of IRX3 was decreased in MAFLD patients.…”
Section: Discussionmentioning
confidence: 99%